2020
DOI: 10.1093/jxb/eraa317
|View full text |Cite
|
Sign up to set email alerts
|

Inducible biosynthesis and immune function of the systemic acquired resistance inducer N-hydroxypipecolic acid in monocotyledonous and dicotyledonous plants

Abstract: Abstract Recent work has provided evidence for the occurrence of Nhydroxypipecolic acid (NHP) in Arabidopsis thaliana, characterized its pathogen-inducible biosynthesis by a three-step metabolic sequence from L-Lys, and established a central role for NHP in the regulation of systemic acquired resistance (SAR). In the present study, we show that NHP is biosynthesized in a series of other plant species in response to microbial attack, generally alongside with its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 58 publications
2
46
0
Order By: Relevance
“…Early grafting experiments demonstrated that the SAR signal(s) can be transmitted from the primary infected leaves of rootstock to distal scion leaves, which is dependent on intact phloem (Guedes et al ., 1980; Tuzun and Kuć, 1985), implying that the phloem is likely the conduit for this long‐distance signal movement. Recent studies on SAR signaling in Arabidopsis showed that the SAR‐inducing signal(s) is present in the phloem sap‐enriched petiole exudates collected from Arabidopsis leaves inoculated with a SAR‐inducing pathogen (Maldonado et al ., 2002; Chaturvedi et al ., 2008; Jung et al ., 2009; Návarová et al ., 2012; Schnake et al ., 2020), further suggesting that the phloem is involved in transmission of the long‐distance SAR signal(s).…”
Section: Long‐distance Defense Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Early grafting experiments demonstrated that the SAR signal(s) can be transmitted from the primary infected leaves of rootstock to distal scion leaves, which is dependent on intact phloem (Guedes et al ., 1980; Tuzun and Kuć, 1985), implying that the phloem is likely the conduit for this long‐distance signal movement. Recent studies on SAR signaling in Arabidopsis showed that the SAR‐inducing signal(s) is present in the phloem sap‐enriched petiole exudates collected from Arabidopsis leaves inoculated with a SAR‐inducing pathogen (Maldonado et al ., 2002; Chaturvedi et al ., 2008; Jung et al ., 2009; Návarová et al ., 2012; Schnake et al ., 2020), further suggesting that the phloem is involved in transmission of the long‐distance SAR signal(s).…”
Section: Long‐distance Defense Signalingmentioning
confidence: 99%
“…Among them, NHP has emerged as the most likely long‐distance signal as mutants defective in NHP biosynthesis were shown to exhibit severely compromised SAR response by independent research groups using different SAR assays (Song, Lu, McDowell, et al ., 2004; Mishina and Zeier, 2006; Jing et al ., 2011; Ding et al ., 2016). NHP biosynthetic genes and NHP are present in diverse plant species, including both monocots and dicots, suggesting that NHP could be a general signaling molecule in SAR (Holmes et al ., 2019; Schnake et al ., 2020). Furthermore, NHP was shown to accumulate in leaf phloem sap of locally inoculated cucumber, supporting a function for NHP as a phloem‐mobile SAR signal (Schnake et al ., 2020).…”
Section: Long‐distance Defense Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…With this magnitude of resistance enhancement in wheat (i.e., approximately 20% reduction of disease severity), NHP treatment could be one of the methods used to jointly control F. graminearum -caused diseases because a single protection solution, such as a completely resistant cultivar or a fungicide that is effective under all conditions, is unavailable. On the other hand, NHP pretreatment in Arabidopsis and tobacco inhibited 90% of the in planta growth of the bacterial pathogen Pseudomonas syringae ( Schnake et al, 2020 ). This implies a difference between NHP actions in wheat and in Arabidopsis /tobacco.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreated with exogenous NHP, these dicotyledonous plants increased resistance to both bacterial and oomycete pathogens ( Hartmann et al, 2018 ). In addition, NHP accumulation was detected in Magnaporthe oryzae -inoculated barley and Brachypodium distachyon , and with exogenous NHP pretreatment, these monocotyledonous plants enhanced resistance to the fungal pathogen M. oryzae ( Schnake et al, 2020 ). These results indicated a potential of using NHP to improve crop resistance to pathogens.…”
Section: Introductionmentioning
confidence: 99%